PENGARUH DURASI PERENDAMAN IKAN GUPPY(Poecilia raticulata) DALAM AIR KELAPA (Cocos nucifera L) TERHADAP EFEKTIFIT - Arnu Finanta; Alis Mukhlis; Paryono Paryono (Jurnal Perikanan Unram, 2020)
The purpose of this study was to determine the effect of differences in the duration of immersion of the best Guppy (Poecilia reticulata) in Coconut Water (Cocos nucifera L) on the effectiveness of masculinization. The method used was experimental with a completely randomized design (CRD) consisting of five treatments and three replications (each treatment was given 40% coconut water), namely treatment A (4 January), treatment B (6 hours), treatment C ( 8 hours), treatment D (10 hours) and treatment E (12 hours). The results of an analysis of variance showed that the difference in the duration of immersion of guppy fish (Poecilia reticulata) with coconut water (Cocos nucifera L) 40% on masculinization showed significantly different results (p <0.05) on male sex ratio and survival rate. The best percentage of males was found in treatment E of 12 hours immersion (93.33%) and the lowest percentage was in treatment A of 4 hours immersion (43.33%) meanwhile, the average survival of all treatments was very good (100%) was not there is death.